Isolation and characterization of antiplasmodial metabolites from South African marine alga - Afolayan, Anthonia Folake (Rhodes University, Faculty of Pharmacy, Pharmacy, 2008)
Malaria is one of the three most deadly diseases in Africa. Although there are available treatments, their efficacy has been greatly reduced over the past two decades due to the development of resistance to currently available drugs. This has necessitated the search for new and effective antimalarial agents. This project approached the search for new antimalarial compounds in two ways: (i) by screening natural products isolated from marine algae against the Plasmodium parasite and (ii) by modification of selected isolated active compounds to target 1-deoxY-Ä‘-xylulose 5-phosphate reductoisomerase (DXR), an enzyme found in the nonmevalonate isoprenoid biosynthetic pathway of Plasmodium Jalciparum. It was envisaged that such a compound would exhibit dual action on the Plasmodium parasite. Extracts obtained from 22 marine algae were prefractionated by solvent partitioning and were screened for anti plasmodial activity against the chloroquine sensitive (CQS) P. Jalciparum D 10 strain. Overall, 50% of the algae screened produced at least one crude fraction with activity against P. Jalciparum. Extracts of the algae Sargassum heterophyllum, Plocamium cornutum, Amphiroa ephedrea and Pterosiphonia cloiophylla gave the most promising results. Fractionation of S. heterophyllum afforded three tetraprenyltoluquinols (3.1, 3.2 and 3.5) and an all-trans-fucoxanthin (3.6). Three new compounds (4.5, 4.6 and 4.7) and two known halogenated monoterpenes (4.1 and 4.4) were isolated from P. cornutum. Each of the isolated compounds from both S. heterophyllum and P. cornutum showed antiplasmodial activity with ICâ‚…â‚€ values ranging from 2.0 - 15.3 Î¼M for S. heterophyllum and 13 - 230 Î¼M for P. cornutum. Attempts to synthetically modify halogenated monoterpene 4.4 by dihydroxylation and phosphorylation in order to inhibit the DXR enzyme was unsuccessful. However, the hemiterpene analogue (5.42) of the halogenated monoterpenes was successfully phosphorylated and dihydroxylated to give compound 5.45 which showed promising activity against DXR. The result obtained indicated that the proposed phosphorylation and dihydroxylation of the halogenated monoterpene 4.4 would result in the synthesis of a potent DXR inhibitor and therefore a potential antimalarial agent with dual mode of action on the Plasmodium parasite.
Keywords: Malaria -- Africa; Antimalarials -- Therapeutic use; Malaria -- Prevention; Malaria -- Drug therapy; Marine algae -- Therapeutic use; Natural products -- Therapeutic use; Plasmodium